Comparative performance analysis of two novel design MIMO antennas for 5G and Wi-Fi 6 applications - Noora Salim; Mandeep J Singh; Hayder Dibs; Amer T. Abed; Mohammad Tariqul Islam; Md. Shabiul Islam (Results in Engineering)
This research provides a comprehensive evaluation of the performance of two Multiple-Input Multiple-Output (MIMO) antenna designs specifically designed for 5G and Wi-Fi 6 technologies. The initial design is a Compact CPW 4 × 4 MIMO Antenna intended for Wi-Fi 6 (IEEE802.11.ax) and 5G (nr77/nr78/nr79) Communications. The second design is a 4 × 4 MIMO Slot Antenna with a Spanner Shape, specifically designed to minimize mutual coupling for Wi-Fi 6 and 5G Communications. The evaluation of these two designs is based on multiple factors including gain, efficiency, bandwidth, and correlation coefficient. The simulation findings indicate that both designs exhibit favourable performance with respect to these criteria. The Compact CPW 4 × 4 MIMO Antenna possesses a gain of 6 dBi, an efficiency of 80%, and a bandwidth of 2.8 GHz. The 4 × 4 MIMO Slot Antenna exhibits a gain of 3.5 dBi, an efficiency of 80%, and a bandwidth of 4.5 GHz. The correlation coefficient between the antennas is low, suggesting a high level of isolation between them. The results indicate that both designs are compatible with 5G and Wi-Fi 6 applications and can offer dependable and effective communication.